J. M. Mason papers - Mason, J. M. (James Murray), 1798-1871.
Chiefly diplomatic communications sent while Mason was Confederate commissioner. Includes correspondence; dispatches; lists of supplies for the Confederate States from London; statements and depositions regarding piracy, claims, the blockade, and other naval and marine matters; cotton bonds and warrants; circulars; and printed matter. Includes instructions to Mason from Confederate officials Judah P. Benjamin, William M. Browne, and R.M.T. Hunter as well as from the British Foreign Office and a 1862 log of the HMS Rinaldo (Sloop). Subjects include the Trent Affair, 1861; British merchant vessels; the actions of the CSS Virginia (Ironclad) at the Battle of Hampton Roads, Va., 1862; and Confederate ships in European waters.
Correspondents include William M. Browne; James Dunwody Bulloch; Alexander Collie; Henry Hotze; Caleb Huse; L.Q.C. Lamar; W.S. Lindsay; A. Dudley Mann; C.G. Memminger; James H. North; Charles O'Conor; John Russell, Earl Russell; George T. Sinclair; John Slidell; James Spence; James Williams; Fraser, Trenholm, and Co. (Liverpool, England); Society for Promoting the Cessation of Hostilities in America (London, England); and Southern Independence Association, Manchester, Eng.
In part typewritten transcripts of papers located elsewhere made for Virginia Mason.
U.S. senator and representative from Virginia and Confederate diplomatic agent in Great Britain.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Benjamin, J. P. -- 1811-1884.; Browne, William M. -- 1823-1883.; Browne, William M. -- 1823-1883 -- Correspondence; Bulloch, James Dunwody, -- 1823-1901 -- Correspondence; Collie, Alexander -- Correspondence; Hotze, Henry, -- 1833-1887 -- Correspondence; Hunter, R. M. T. -- 1809-1887.; Huse, Caleb, -- 1831-1905 -- Correspondence; Lamar, L. Q. C. -- 1825-1893 -- Correspondence; Lindsay, W. S. -- 1816-1877 -- Correspondence; Mann, A. Dudley -- 1801-1889 -- Correspondence; Memminger, C. G. -- 1803-1888 -- Correspondence; North, James H. -- Correspondence; O'Conor, Charles, -- 1804-1884 -- Correspondence; Russell, John Russell, -- Earl, -- 1792-1878 -- Correspondence; Sinclair, George T. -- Correspondence; Slidell, John, -- 1793-1871 -- Correspondence; Spence, James, -- 1811-1876 -- Correspondence; Williams, James, -- 1796-1869 -- Correspondence; Great Britain. -- Foreign Office; Fraser, Trenholm, and Co. (Liverpool, England) -- Correspondence; Rinaldo (Sloop); Society for Promoting the Cessation of Hostilities in America (London, England) -- Correspondence; Southern Independence Association -- Correspondence; Virginia (Ironclad); Claims; Cotton trade -- Confederate States of America; Hampton Roads, Battle of, Va., 1862.; Merchant marine -- Great Britain; Pirates; Trent Affair, 1861.; Confederate States of America -- Commerce -- Great Britain; Confederate States of America -- Foreign relations -- Great Britain; Confederate States of America -- History, Naval; Great Britain -- Commerce -- Confederate States of America; Great Britain -- Foreign relations -- Confederate States of America; United States -- History -- Civil War, 1861-1865 -- Blockades; United States -- History -- Civil War, 1861-1865 -- Naval operations; Virginia -- History -- Civil War, 1861-1865.; Representatives, U.S. Congress -- Virginia; Senators, U.S. Congress -- Virginia